Strabismus Surgery and its Complications - Coats, David K. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Strabismus Surgery and its Complications is divided into two is provided based on evidence-based medicine where available. distinct sections. Part I outlines the surgical management of Consensus and/or common sense advice is provided where - strabismus in 17 chapters. A full range of topics is covered idence-based medicine is not available. A chapter on managing including basic anatomy and physiology, surgical planning, patients with atypical and unexpected anatomical features and preoperative and postoperative management, and surgical a chapter on the medicolegal aspects of strabismus surgery are techniques. Surgical techniques are described in dedicated included. Te textbook is extensively referenced and indexed chapters, each richly illustrated with fgures and photographs. to facilitate rapid identifcation and review of desired inform -a Detailed descriptions of the basic steps of surgery as well as tion. Cross-reference is made throughout each chapter to other surgical nuances are provided. Te fgures and fgure legends chapters containing related information. are designed to stand alone as basic surgical instruction for the A DVD is provided containing video footage of basic su- surgeon who has experience with the surgical management of gical techniques to compliment the information on surgical strabismus. More detailed instruction is available in the text for techniques provided in Part I of the textbook. Te DVD also those wanting elaboration.